Study of yellow leaf virus disease on eggplant (Solanum melongena L.) in West Sumatra - Najmi, Lailatun; Sari, Silvia Permata; Yaherwandi, Yaherwandi (Agrovigor, 2024)
Yellow leaf virus disease, accompanied by vector insect attacks, was the leading cause of the current decline in eggplant production. Yellow leaf virus disease spreads more quickly due to the influence of insect vectors. The research aims to determine the type of insect vector that spreads yellow leaf virus disease and the incidence and severity of yellow leaf virus disease on eggplants in West Sumatra. This research method uses a survey method for five months in 2023. The sample was taken diagonally with five observation points. At each point, five plant samples were taken randomly. Observations were carried out three times at four locations representing the centers of eggplant production areas in West Sumatra, namely in Kuranji District, Pauh District, Batang Anai District, and Sitoga District. Five different vector insect species were discovered, along with their corresponding population sizes, according to the observations: Bemisia tabaci (5846 individuals), Amrasca sp. (1199 individuals), Thrips sp. (176 individuals), Paracoccus sp. (43 individuals), and Aphids gosypii (34 individuals). The incidence of the disease reached 90% with the severity of the disease being 42.45% in Sitoga District. The highest disease severity was 43.94% in Kuranji District, with an incidence of the disease of 70%. This research helps implement strategies to control yellow leaf virus disease by determining the threshold for the influence of the number of vector insect populations in increasing the incidence and severity of yellow leaf virus disease in eggplants.